TXH11106: A Third-Generation MreB Inhibitor with Enhanced Activity against a Broad Range of Gram-Negative Bacterial Pathogens - Eric J. Bryan; Hye Yeon Sagong; Ajit K. Parhi; Mark C. Grier; Jacques Y. Roberge; Edmond J. LaVoie; Daniel S. Pilch (MDPI AG, 2022)
The emergence of multi-drug-resistant Gram-negative pathogens highlights an urgent clinical need to explore and develop new antibiotics with novel antibacterial targets. MreB is a promising antibacterial target that functions as an essential elongasome protein in most Gram-negative bacterial rods. Here, we describe a third-generation MreB inhibitor (TXH11106) with enhanced bactericidal activity versus the Gram-negative pathogens Escherichia coli, Klebsiella pneumoniae, Acinetobacter baumannii, and Pseudomonas aeruginosa compared to the first- and second-generation compounds A22 and CBR-4830, respectively. Large inocula of these four pathogens are associated with a low frequency of resistance (FOR) to TXH11106. The enhanced bactericidal activity of TXH11106 relative to A22 and CBR-4830 correlates with a correspondingly enhanced capacity to inhibit E. coli MreB ATPase activity via a noncompetitive mechanism. Morphological changes induced by TXH11106 in E. coli, K. pneumoniae, A. baumannii, and P. aeruginosa provide further evidence supporting MreB as the bactericidal target of the compound. Taken together, our results highlight the potential of TXH11106 as an MreB inhibitor with activity against a broad spectrum of Gram-negative bacterial pathogens of acute clinical importance.